Deformation behavior of modified 9Cr–1Mo steel under low cycle fatigue at 600 °C - Verma P.; Basu J.; Santhi Srinivas N.C.; Singh V. (My University, 2025)
Low cycle fatigue (LCF) behavior of the modified 9Cr–1Mo steel was studied in normalized & tempered condition in the regime of low strains, at total strain amplitudes from ± 0.25% to ± 0.50%, at 600 °C. At lower strain amplitudes this steel exhibited stabilized stress response in the initial stage followed by softening till failure. However, at high strain amplitudes, there was continuous softening from the first cycle till the failure. Cyclic stress response increased with increase in strain rate from 10− 3 s− 1 to 10− 2 s− 1, and the fatigue life was reduced at the lower strain rate of 10− 3 s− 1. The fracture surface was oxidized, which is assumed to play a major role in the life reduction, in particular, at the lower strain rate. TEM investigation of the fatigue tested specimens revealed that cyclic softening was associated with many factors such as cell formation, dynamic recovery/recrystallization, grain rotation, coarsening of carbides and annihilation of the arrays of dislocations. © 2017 Elsevier Inc.